Иммунно-биохимические факторы риска прогрессирования диабетической ретинопатии у больных с сахарным диабетом - Ярошева, Н.А. (Таврический медико-биологический вестник, 2014)
Обстежено 119 хворих з ДР розділених на групи дослідження. Контролем служили 24 здорових
донора у відповідному віковому діапазоні. Встановлено, що важливою патогенетичною складової
прогресування ДР є наростання системного рівня прозапальних цитокінів IL-1β і TNF-α, дефіцит
фібринолітичних ферментів, збільшення рівня Et-1 і vWf в плазмі крові залежно від стадії захворювання,
що сприяє збільшенню гіпоксичних процесів в тканинах ока і є, в свою чергу, імунно-біохімічними
факторами ризику прогресування ДР у хворих з ЦД. 119 patients with DR divided on research groups are examined. As a control group was 24 healthy donors
in the conforming age range. It is determined that an important pathogenetic component of DR progressing is
increase of systemic level of proinflammatory cytokines IL-1β and TNF-α, deficiency of fibrinolytic ferments,
increase of Et-1 and vWf level in blood plasma depending on a disease stage that promotes to aggravation of
hypoxic processes in eye’s tissues and in its turn is immuno-biochemical risk factors of DR progressing in
patients with DM.